2018
DOI: 10.1007/s13300-018-0373-9
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness and Safety of a Novel Care Model for the Management of Type 2 Diabetes at 1 Year: An Open-Label, Non-Randomized, Controlled Study

Abstract: IntroductionCarbohydrate restriction markedly improves glycemic control in patients with type 2 diabetes (T2D) but necessitates prompt medication changes. Therefore, we assessed the effectiveness and safety of a novel care model providing continuous remote care with medication management based on biometric feedback combined with the metabolic approach of nutritional ketosis for T2D management.MethodsWe conducted an open-label, non-randomized, controlled, before-and-after 1-year study of this continuous care in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
450
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(531 citation statements)
references
References 48 publications
14
450
1
13
Order By: Relevance
“…Of these, all 13 studies set initial CHO amount to <50 g/d before increasing or decreasing CHO intake. For example, Hallberg et al 2018 commenced participants on a CHO intake <30 g/d before personalizing the prescriptions according to the goal of achieving nutritional ketosis (beta hydroxybutyrate level of 0.5‐3.0 mmol/L).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, all 13 studies set initial CHO amount to <50 g/d before increasing or decreasing CHO intake. For example, Hallberg et al 2018 commenced participants on a CHO intake <30 g/d before personalizing the prescriptions according to the goal of achieving nutritional ketosis (beta hydroxybutyrate level of 0.5‐3.0 mmol/L).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies (11/21) did not intentionally reduce or minimize saturated fat but recommended a variety of fat from whole food sources (including fatty cuts of meat, oily fish, full‐fat cheese, cream, coconut oil, olive oil, nuts, seeds and avocado). One study specifically reported providing advice on adequate intakes of omega‐3 and omega‐6 polyunsaturated fats …”
Section: Resultsmentioning
confidence: 99%
“…More recently, a non‐randomised, controlled study using a novel remote care model, which included a well‐formulated ketogenic diet compared with usual care, showed the ketogenic diet achieved T2D remission in 25% of participants compared with no cases in the usual care group (Hallberg et al . ). Similar to the results of the Look AHEAD trial, remission rates reduced over time in both studies (Esposito et al .…”
Section: Type 2 Diabetes and Very Low‐energy And Low‐energy Dietsmentioning
confidence: 97%
“…Regarding unpublished data, Mr Inkinen revealed that new results were just received internally; although no exact numbers or outcomes were divulged, he did share that the company now treats patients in 49 of the 50 states in the US. Previously published 1‐year results from Virta demonstrated 60% type 2 diabetes reversal, 1.3% HbA1c reduction (baseline 7.6%), 12% weight loss (approximately 14 kg), and significant improvement in 22 of 26 cardiovascular risk factors at 1 year …”
Section: Health 20 2018mentioning
confidence: 94%